(untitled) (Itinera, 2020)
Where does color exist? As a property of light in "red wavelengths," as a neural calculation by retinal photoreceptors, or as a calculation in the brain? The perceptual couplings of synesthesia, along with color constancy and colored shadows, suggest that color is not a property of objects: In order to be biologically useful within our environment of ever–changing illumination, the brain must assign stable colors to surfaces. Color exists only within the silent darkness of an individual skull. Richard E. Cytowic, MD MFA is Clinical Professor of Neurology at George Washington University, and the author most recently of “Synesthesia” and “Wednesday is Indigo Blue” (MIT Press).